A review of surface roughness impact on dielectric film properties. Issue 1 (10th July 2021) - Song, Guanghui; Wang, Yaojin; Tan, Daniel Q.
Abstract: The importance of surface roughness with respect to the bulk properties of dielectric materials is often overlooked. Surface roughness or interfaces between different material layers often significantly affects the external properties of thin films. Surface roughness holds its commonalty and critical impact among many materials properties. This review summarises the recent work on the effect of surface roughness on the mechanical, thermal, physical, and dielectric properties of dielectric films. Appropriate roughness favours adhesion, filtration, biological fouling, tribological properties, and magnetic properties. Nevertheless, lower roughness generally benefits the dielectric properties of dielectric materials, with thicknesses ranging from a few nanometres to up to 50 μm. This review discusses surface roughness control and the techniques of measurement as well. It emphasises the importance and characterisation of sample surface roughness for a better understanding of the dielectric phenomenon, mechanisms, and electrical stress test setup for various dielectric films.